1988
DOI: 10.1063/1.341539
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-quality amorphous silicon films by evaporative silane surface decomposition

Abstract: High-quality hydrogenated amorphous silicon films (a-Si:H) have been produced by decomposition of low-pressure silane gas on a very hot surface with deposition on a nearby, typically 210 °C substrate. A high-temperature tungsten filament provides the surface for heterogeneous thermal decomposition of the low-pressure silane and subsequent evaporation of atomic silicon and hydrogen. These evaporated species (primarily) induce a-Si:H growth on nearby substrates which are temperature controlled using a novel subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(97 citation statements)
references
References 25 publications
7
89
0
1
Order By: Relevance
“…The accumulated silicon atoms can react with or diffuse into the metal wires, forming metal silicon alloy or metal silicide. At an even lower temperature or at a very high silane partial pressure, depending on the type of filament, liquid silicon may appear on the filament surface, which further reduces the filament's catalytic ability [10,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulated silicon atoms can react with or diffuse into the metal wires, forming metal silicon alloy or metal silicide. At an even lower temperature or at a very high silane partial pressure, depending on the type of filament, liquid silicon may appear on the filament surface, which further reduces the filament's catalytic ability [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…For a fresh filament at a high enough filament temperature, all silane molecules are decomposed within a few collisions with the hot-wire surface, resulting in a significant amount of atomic Si and H evaporating to the gas phase [10]. At a moderate filament temperature, most of the SiH 4 molecules are also dissociated upon collision with the filament surface, but the evaporation of silicon atoms becomes slower, as insufficient energy is available for silicon to immediately desorb from the filament surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of recent reports [3][4][5][6] of the distribution of wire-desorbed radicals, following the early report by Doyle et al 7 Experiments conducted using similar detection schemes, such as vacuum ultraviolet photoionization mass spectrometry, have shown quite different results in some cases. 4,5 Whether these differences are due to the different histories of the wire used or differences in the reactor condition ͑e.g., amorphous silicon-coated walls͒ is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Doyle et al [1] have observed that SiH 4 dissociation is high than at lower pressure than at higher pressure. This, they explain in terms of the availability of reaction sites on the filament surface.…”
Section: Resultsmentioning
confidence: 99%